The hitchhiker's guide to the galaxy - Adams, Douglas, 1952-2001. (New York : Ballantine Books, 2009)
Chronicles the off-beat and occasionally extraterrestrial journeys, notions, and acquaintances of galactic traveler Arthur Dent.
Keywords: Prefect, Ford -- Fiction; Dent, Arthur -- (Fictitious character) -- Fiction; Humorous fiction; Science fiction